PANCASILA SEBAGAI ORTHODOKSI DAN ORTHOPRAKSIS DALAM KEHIDUPAN BERBANGSA DAN BERNEGARA - Mulyono, Mulyono (HUMANIKA, 2016)
Pancasila as ideology contains many teachings about how human should relate to the others, nature and God in the life of society and the state. Pancasila’s teachings believed truth and goodness by Indonesian peoples since been justified through a variety of scientific-philosophical studies. This is the meaning of Pancasila as a orthodoxy. On the other hand, the process of modernization spur the development of science and technology and phenomenon of globalization so that dynamics and changes in society take place quickly. In the context of practical guideline, the implementation of Pancasila should adapt to the development of national and international community. The breakdown of Pancasila’s values should be reconstructed continuously order to always stay relevant as problem solver and able to keep up with the the times. Revitalization and reinterpretation of Pancasila as a ideology should always be done in order to not become obsolete so abandoned by its adherents.